REKAYASA LINGKUNGAN DENGAN NAUNGAN TERTUTUP UNTUK PERBAIKAN KUALITAS DAN PRODUKTIVITAS TEMBAKAU RAKYAT DI SLEMAN, JOGJAKARTA - Sudaryono, Sudaryono (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2004)
General the effort in agriculture area has involved not only small failure risk of crop, the risk might be in the form of pest disturbance or crop disease, floods, dryness, and uncertain climate disturbance. To solve the tobacco crop in the climate problems (especially micro climate), was made experiment by engineering technology of physical environment (micro climate), with closed shade technology in order to obtain an optimal production. The field result experiment, in application of the closed shade technology, in reality hasgiven positive impact to tobacco production. It is showed by the change of indicator of crop production, through season : growth acceleration of leaf, which is better than tobacco crop planted outside of the shade